Assessing the effect of reducing agents on the selective catalytic reduction of NOx over Ag/Al2O3 catalysts. Issue 6 (6th November 2015) - D'Agostino, Carmine; Chansai, Sarayute; Bush, Isabelle; Gao, Chensong; Mantle, Mick D.; Hardacre, Christopher; James, Stuart L.; Gladden, Lynn F.
Abstract : The selective catalytic reduction (SCR) of NO x in the presence of different reducing agents over Ag/Al2 O3 prepared by wet impregnation was investigated by probing catalyst activity and using NMR relaxation time analysis. Abstract : The selective catalytic reduction (SCR) of NO x in the presence of different reducing agents over Ag/Al2 O3 prepared by wet impregnation was investigated by probing catalyst activity and using NMR relaxation time analysis to probe the strength of surface interaction of the various reducing agent species and water. The results reveal that the strength of surface interaction of the reducing agent relative to water, the latter present in engine exhausts as a fuel combustion product and, in addition, produced during the SCR reaction, plays an important role in determining catalyst performance. Reducing agents with weak strength of interaction with the catalyst surface, such as hydrocarbons, show poorer catalytic performance than reducing agents with a higher strength of interaction, such as alcohols. This is attributed to the greater ability of oxygenated species to compete with water in terms of surface interaction with the catalyst surface, hence reducing the inhibiting effect of water molecules blocking catalyst sites. The results support the observations of earlier work in that the light off-temperature and maximum NO x conversion and temperature at which that occurs are sensitive to the reducing agent present during reaction, and the proposal that improved catalyst performance is caused by increased adsorption strength of the reducing agent, relative to water, at the catalyst surface. Importantly, the NMR relaxation time analysis approach to characterising the strength of adsorption more readily describes the trends in catalytic behaviour than does a straightforward consideration of the polarity ( i.e., relative permittivity) of the reducing agents studied here. In summary, this paper describes a simple approach to characterising the interaction energy of water and reducing agent so as to aid the selection of reducing agent and catalyst to be used in SCR conversions.